Global, regional, and national burden of vitamin A deficiency (1990–2021) and projections to 2042: associations with sociodemographic development - Qin, Ningjing; Chen, Liwei; Guo, Jin; Wang, Jiabi; He, Yujun (Frontiers in Nutrition, 2025)
BackgroundVitamin A deficiency (VAD) remains a significant public health concern. Currently, there is a lack of comprehensive, up-to-date global assessments on the specific burden of VAD.ObjectiveThis study aims to quantify the global, regional, and national disease burden attributable to VAD from 1990 to 2021, analyze its association with sociodemographic development, and project trends through 2042.MethodUsing the Global Burden of Disease (GBD) 2021 database, we extracted data on deaths and disability-adjusted life years (DALYs) attributable to VAD across 204 countries and territories. We calculated absolute numbers, age-standardized rates (ASRs), estimated annual percentage changes (EAPCs), and relative changes of number and ASR at global, regional, socio-demographic index (SDI) quintile, and national levels. Pearson correlation and frontier analysis were used to examine the relationship between VAD burden and SDI. Bayesian age-period-cohort models were employed to project ASRs through 2042.ResultsBetween 1990 and 2021, the global number of deaths attributable to VAD decreased from 188458.416 to 17374.404; the ASR declined from 3.04 to 0.27 per 100,000 population (EAPC: −7.81%). Globally, VAD-attributable DALYs decreased from 18.79 million to 2.63 million, with the ASR falling from 303.72 to 40.10 per 100,000 population (EAPC: −6.70%). The largest reductions were observed in East Asia, Southeast Asia, and high-middle SDI regions, whereas the smallest reductions occurred in low SDI regions and Oceania. The burden consistently remained higher in males than in females, though this gap narrowed over time. Diarrheal diseases as the leading cause of VAD-attributable deaths. A strong negative correlation was identified between SDI and VAD burden; frontier analysis highlighted top-performing countries at equivalent SDI levels, which could serve as benchmarks. Projections indicated that VAD-attributable deaths and DALYs will continue to decline by 2042.ConclusionSince 1990, global VAD-attributable mortality and DALYs have declined significantly, driven by socioeconomic development and public health interventions. However, substantial inequalities persist, with low SDI regions and males bearing a disproportionate residual burden. Sustained investment in targeted nutrition programs integrated with infectious disease control alongside broader socioeconomic development, particularly in the poorest settings, is necessary to accelerate progress toward eliminating VAD as a public health threat.